Species identification approach for both raw materials and end products of herbal supplements from Tinospora species - Maslin Osathanunkul; Rossarin Osathanunkul; Panagiotis Madesis (BMC, 2018)
Abstract Background Nowadays herbal products used in traditional medicine are sold in processed forms and thus morphological authentication is almost impossible. With herbal industry rapidly growing size, consumer safety becomes an important issue that requires special attention. Identification of herbal species in the products is therefore needed. Methods Sequences from the selected regions (matK, rbcL, trnL and ITS1) were retrieved and analysed. Then the most suitable barcode was assessed for discrimination of T. crispa from closely related species by HRM analysis and used in authentication of commercial products. Results The ITS1 barcode was found to be the suitable primer as melting data from the HRM assay proved to be capable of distinguishing T. crispa from its related species. The developed protocol was then employed to authenticate medicinal products in powdered form. HRM analysis of all tested samples here revealed that five out of eight products contained not only the indicated species T. crispa but also other Tinospora, that have a high level of morphological similarity. Conclusion Misrepresentation, poor packaging and inappropriate labeling of the tested medicinal herbal products are thought to be the reason of the results here. Using Bar-HRM with the ITS marker lead to success in authenticating the tested herbal products.